The conserved Wobble uridine tRNA thiolase Ctu1–Ctu2 is required to maintain genome integrity - Dewez, Monique (National Academy of Sciences, 2008)
Modified nucleosides close to the anticodon are important for the proper decoding of mRNA by the ribosome. Particularly, the uridine at the first anticodon position (U34) of glutamate, lysine, and glutamine tRNAs is universally thiolated (S(2)U34), which is proposed to be crucial for both restriction of wobble in the corresponding split codon box and efficient codon–anticodon interaction. Here we show that the highly conserved complex Ctu1–Ctu2 (cytosolic thiouridylase) is responsible for the 2-thiolation of cytosolic tRNAs in the nematode and fission yeast. In both species, inactivation of the complex leads to loss of thiolation on tRNAs and to a thermosensitive decrease of viability associated with marked ploidy abnormalities and aberrant development. Increased level of the corresponding tRNAs suppresses the fission yeast defects, and our data suggest that these defects could result from both misreading and frame shifting during translation. Thus, a translation defect due to unmodified tRNAs results in severe genome instability.